The effect of cross fit training on anaerobic power and dynamic balance of greco-roman and freestyle wrestlers - Caloglu, M.; Yüksel, O. (International Journal of Applied Exercise Physiology, 2020)
Aim; CrossFit is a sports branch which started as a training model and constituted its discipline by increasing gradually. The present study aims to examine the anaerobic power and dynamic balance changes of freestyle and Greco-Roman wrestlers who perform CrossFit training.